Characterization of T-cell immune responses against Staphylococcus chromogenes naturally-induced subclinical mastitis in dairy cows - Yu, Chen; Wu, Jie; Zhang, Sheng; Ye, Chunmei; Wei, Guojun; Yang, Zhangping; Zhang, Zhipeng (Frontiers in Immunology, 2025)
IntroductionSubclinical mastitis in dairy cows is an asymptomatic inflammatory condition of the mammary gland during lactation. It is frequently associated with reduced milk yield, impaired milk quality, and an elevated risk of progression to clinical mastitis. The dysregulation of immune homeostasis characterizing this subclinical state represents a significant yet often overlooked concern in dairy herds.MethodsWe characterized T cell subsets in cows with Staphylococcus chromogenes-induced subclinical mastitis and healthy controls.ResultsWe found that S. chromogenes infection induced an increase in the percentage of γδ T cells and a decrease in CD4+CD8+ double-positive (DP) T cells within milk cells, while significantly elevating the percentage of γδ T cells expressing CD44. Cell sorting combined with quantitative RT-PCR has indicated that infection by S. chromogenes may activate γδ T cells. Specifically, in subclinical mastitis milk, the expression levels of five cytokines—IFN-γ, IL-2, TNF-α, IL-17, and GZMB—were significantly higher in WC1+ γδ T cells compared to healthy cows. Furthermore, these cells released elevated levels of PRF1, which directly killed target cells infected with bacteria compared to the levels observed in healthy cows.DiscussionOur results reveal, for the first time, the significant role of γδ T cells in S. chromogenes -induced subclinical mastitis, providing new insights into the immune protective mechanisms against subclinical mastitis in cows.